Therapeutic potential of magnesium sulfate in improving duodenal homeobox 1 and PPARG coactivator 1 alpha genes to reduce pancreatic insulin resistance in F1 offspring of diabetic rats - Mahtab Ghanbari Rad; Hossein Rezazadeh; Mohammadreza Sharifi; Nepton Soltani (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): The study aimed to investigate the role of magnesium sulfate (MgSO4) therapy in pancreatic insulin resistance (IR) in diabetic and non-diabetic rats and their F1 offspring following administration of a high-fat diet (HFD). Materials and Methods: Diabetes was induced in the subjects through a combination of HFD and a low dose of streptozotocin (STZ). The male and female diabetic animals were divided into three groups: diabetic control (DC), insulin, and MgSO4 (Mg) treated groups. One group of both sexes was kept as non-diabetic control (NDC) and fed a regular diet. Their F1 offspring were fed a regular diet for four months. Euglycemic hyperinsulinemic clamp (HEC) tests were performed on the parents and their F1 offspring. Blood samples were taken every hour during the clamp to measure changes in glucagon levels. Pancreas tissue was isolated, and the expression of pancreatic and duodenal homeobox 1(Pdx1) and PPARG coactivator 1 alpha (Pgc1α) genes was measured in all groups. Results: Treatment with MgSO4 or insulin decreased HOMA-IR, TyG index, BGL, ITT, HbA1c, glucagon level, Pgc1α expression, and increased glucose infusion rate (GIR), body weight, Pdx1 gene expression, and insulin level in diabetic parents and their F1 offspring compared to the DC group. These changes suggest a decrease in IR. Additionally, alterations in IR have decreased. Also, changes in the expression of these genes indicate a positive impact on the survival and regeneration rate of pancreatic β cells.Conclusion: MgSO4 showed beneficial effects in treating glucose metabolism and improving IR.